Procedure for making a cement mixture with recycled plastics applicable to the manufacture of building elements - Gaggino, Rosana (2010)
This review is about the Argentina Patent number AR 047617B1 published on August 12, 2008. Its inventors are Gaggino Rosana, Arguello Ricardo and Berretta Horacio. The topic is a procedure to make new constructive elements (bricks and plates) by using these recycled plastics: - Low-density polyethylene (LDPE), recycled out of discarded soft drink packs. - Polyethylene-terephthalate (PET), recycled out of discarded soft drink bottles. - Several plastics, from the printed films used, like packages of candies (remainder of production plant by faults of inked or thickness). These conveniently grounded plastics were taken as aggregates to be mixed with Normal Portland cement, replacing heavy sand and gravel habitually used in these mixtures. These materials can be used in constructive elements such as bricks and plates for economic houses closures or traditional construction. The developed constructive elements offer high thermal insulation, so they can be used in closures with a smaller thickness than conventional bricks and blocks. Besides, they have a lower specific weight than these traditional constructive elements. Recycling means lowering costs, making part of the environment contaminating waste useful and providing the unemployed and/or unqualified work force with jobs through uncomplicated technologies. Therefore, it has an economical as well as ecological and socially concerned proposal.